Fetal death in utero: epidemiological aspects, management and maternal prognosis in the obstetrics and gynecology department of the community medical centre of Ratoma - Diallo, Boubacar Alpha; Diallo, Boubacar Siddy; Sow, Ibrahima Sory; Bah, Ibrahima Koussy; Baldé, Ibrahima Sory; Diallo, Abdrahmane; S. Y., Telly; Keita, N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Fetal death in utero (FDIU) often represents a tragedy badly lived, sometimes incomprehensible. It is considered as a failure of pregnancy’s progress and monitoring. It is a frequent problem in obstetrical practice. Objective of study was to contribute to the study of FDIU in the maternity ward of the Ratoma municipal medical center. Methods: This was a prospective study of analytical type conducted over a period of 6 months from 1 January to 30 June 2017. Results: During this study period, we recorded 54 cases of FDIU out of a total of 1256 deliveries, or a frequency of 4.3%. The average age of our patients was 28.5 years with extremes of 16 to 39 years, the most represented age group was 25 to 34 years, with a frequency of 44.4%. The absence of active fetal movement was the main reason for consultation, with a frequency of 51.9%, and housewives were the most affected, with a frequency of 61.1%. The 70.4% of our patients gave birth by vaginal delivery and oxytocin was the most commonly used drug for induction of labor, i.e., 77.8%. The immediate maternal prognosis was 100% favorable and no case of maternal death was recorded Conclusions: In-utero fetal death is a frequent obstetrical pathology, the awareness of women for the realization of ANC as well as the early management of risk factors detected during ANC constitutes an element of great importance. Therefore, a regular follow-up of all pregnant women even in the absence of risk factors proves necessary.